PENGEMBANGAN MEDIA FLASHCARD PADA PEMBELAJARAN BAHASA INDONESIA MEMBACA PERMULAAN PESERTA DIDIK KELAS II MI MA’ARIFUL ULUM - Jeny Talia; Nurlaila; Djoko Rohadi Wibowo (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to develop flashcard learning media that are valid, practical, and effective in improving the beginning reading skills of second-grade students at MI Ma’ariful Ulum on the topic of invitation expressions in Indonesian language learning. This study employed the Research and Development (R&D) method using the ADDIE development model, consisting of Analysis, Design, Development, Implementation, and Evaluation. Data were collected through validation questionnaires completed by material experts, language experts, and media experts, as well as student response questionnaires to measure practicality. The effectiveness of the media was assessed using oral pre-test and post-test, which were analyzed using the Normalized Gain (N-Gain) formula. The validation results indicated that the flashcard media met the “very valid” criteria, with scores of 90% from the material expert, 80% from the language expert, and 88% from the media expert, resulting in an overall average of 86%. The practicality test based on student responses showed an average score of 92%, categorized as “very practical.” Furthermore, the effectiveness test revealed a significant improvement in students’ beginning reading skills, with an average N-Gain score of 79.13%, which falls into the “high” category and is classified as “effective.” Therefore, the developed flashcard learning media are highly valid, very practical, and effective in improving beginning reading skills and increasing students’ interest in learning.